Limits of buyer-driven governance for sustainability: inherent challenges of fragmented supplier networks. (23rd October 2021) - Alexander, Rachel
Abstract: This article questions retailers' role as buyers driving production. Exploring a network involving Indian suppliers of UK retailers' cotton garments, limitations preventing coercive buyer power from controlling production practices are identified. Overall, the dominant system of large-scale fragmented supplier networks connecting raw materials to final products accommodates commercially viable practices causing social or environmental challenges. While some pressures effectively span complex networks, buyers' practice-related demands do not. Dissecting the 'drivenness' concept, this study shows multipolar governance within an industry often considered buyer-driven. Also, it furthers critiques of private governance's effectiveness, indicating the need for alternative governance frameworks or network structures.